Association of platelet-to-lymphocyte ratio and neutrophil-to-lymphocyte ratio with outcomes in stroke patients achieving successful recanalization by endovascular thrombectomy - Ma, Jin; Guo, Wenting; Xu, Jiali; Li, Sijie; Ren, Changhong; Wu, Longfei; Wu, Chuanjie; Li, Chuanhui; Chen, Jian; Duan, Jiangang; Ma, Qingfeng; Song, Haiqing; et al. (Frontiers in Neurology, 2022)
Objective Serum inflammatory biomarkers play crucial roles in the development of acute ischemic stroke (AIS). In this study, we explored the association between inflammatory biomarkers including platelet-to-lymphocyte ratio (PLR), neutrophil-to-lymphocyte ratio (NLR), and monocyte-to-lymphocyte ratio (MLR), and clinical outcomes in AIS patients who achieved successful recanalization. Methods Patients with AIS who underwent endovascular thrombectomy (EVT) and achieved a modified thrombolysis in the cerebral infarction scale of 2b or 3 were screened from a prospective cohort at our institution between January 2013 and June 2021. Data on blood parameters and other baseline characteristics were collected. The functional outcome was an unfavorable outcome defined by a modified Rankin Scale of 3–6 at the 3-month follow up. Other clinical outcomes included symptomatic intracranial hemorrhage (sICH) and 3-month mortality. Multivariable logistic regression analysis was performed to evaluate the effects of PLR, NLR, and MLR on clinical outcomes. Results A total of 796 patients were enrolled, of which 89 (11.2%) developed sICH, 465 (58.4%) had unfavorable outcomes at 3 months, and 168 (12.1%) died at the 3-month follow up. After adjusting for confounding variables, a higher NLR (OR, 1.076; 95% confidence interval [CI], 1.037–1.117; p < 0.001) and PLR (OR, 1.001; 95%CI, 1.000–1.003; p = 0.045) were significantly associated with unfavorable outcomes, the area under the receiver operating characteristic curve of NLR and PLR was 0.622 and 0.564, respectively. However, NLR, PLR, and MLR were not independently associated with sICH and 3-month mortality (all adjusted p > 0.05). Conclusion Overall, our results indicate that higher PLR and NLR were independently associated with unfavorable functional outcomes in AIS patients with successful recanalization after EVT; however, the underlying mechanisms are yet to be elucidated.